The Correlation Between Screen Time, Sleep Quality, and Physical Fitness Among Grade VII Students - Niko Bagaskara; Hijrah Maulidiah Afifah (Universitas Negeri Semarang, 2026)
This study aims to examine the relationship between screen time and sleep quality as well as physical fitness levels of seventh-grade students at SMP Negeri 1 Semarang. This research employed a quantitative approach with a correlational design. The population consisted of 287 students, and 74 students were selected as the sample using simple random sampling based on the Slovin formula with a 10% margin of error. Data were collected through questionnaires to measure screen time and sleep quality, as well as a physical fitness test to assess students’ fitness levels. Data were analyzed using Pearson Product Moment correlation at a significance level of 0.05. The results indicated a significant relationship between screen time and sleep quality (r = 0.234; p = 0.045) with a low correlation level, and a significant relationship between screen time and physical fitness levels (r = -0.354; p = 0.002) with a moderate correlation level. The coefficient of determination showed that screen time contributed 5.48% to sleep quality and 12.53% to physical fitness levels. Overall, screen time plays a significant role in students’ sleep quality and physical fitness levels.